STRATEGI PENANGANAN KESEHATAN MENTAL DALAM MENGATASI ANXIETY PADA SANTRI DI PONDOK PESANTREN - Nurul Asma Khoiriyah; Mahasri Shobahiya (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The mental health of students at the Al-Amin Islamic Boarding School in Palur is a serious concern due to academic pressure and environmental adaptation challenges that trigger anxiety disorders. The focus of this study is to identify triggers for psychological anxiety and evaluate the management strategies implemented by caregivers. This research uses a qualitative case study approach through in-depth interviews, participant observation, and descriptive documentation analysis. The research findings reveal that students' anxiety stems from the demands of public speaking, exams, and the dynamics of social interactions. Management strategies are implemented through three main pillars: providing consistent moral support, a spiritual approach through routine Tahajud prayers and dhikr, and providing private counseling facilities. The results indicate that although spiritual interventions are very effective in calming the mind, barriers such as mental health stigma and family reluctance to provide internal student data still hinder optimal recovery. The main conclusion emphasizes that managing anxiety in Islamic boarding schools requires a more structured early detection system and open communication patterns between the institution and parents. Strengthening professional mental health facilities is urgently needed to ensure that students are able to develop their potential in a healthy, resilient, and balanced manner amidst the dynamics of rigorous dormitory life in a sustainable manner for their future through the integration of psychological services and complete spiritual recovery for education.